Baalbek, Libanon. Kleinere Forschungen, Konservierungsarbeiten im Bustan Nassif und Aufarbeitung der Arbeiten 2001 bis 2012. Die Arbeiten der Jahre 2017 und 2018 - van Ess, Margarete (e-Forschungsberichte des DAI, 2018)
In Baalbek, a conservation project for the archaeological area “Bustan Nassif”, a living quarter mainly of the Ayyubid and Mameluk Periods was continued and completed in 2018. It offered training in technics of building conservation as well as in the maintenance of archaeological architectural structures. The project adds to a comprehensive project of the Lebanese Council for Development and Reconstruction as well as of the Department General for Archaeology that aims at presenting additional archaeological areas to visitors and a modernization of the visitor’s fascilities. The Lebanese-German conservation project has been generously funded by the German Foreign Office.